Serum Lactate Level as a Predictor of Outcome in Patients with Septic Shock - Bhandari, Rupak; Bhandari, R; Paudel, M; Malla, G B (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Sepsis and Septic shock are a common presentation in the Emergency Department with high morbidity and mortality. Serum lactate level increases substantially in the patients with septic shock. The objectives of this study were to determine serum lactate levels at the time of presentation, find out the outcome and correlate lactate levels with the outcome in the patients with septic shock.Methods: It is a prospective cross-sectional study of patients presenting to the Emergency, who met the criteria for septic shock defined by Surviving Sepsis Guidelines 2012. Patients’ demographics, co morbidity, triage vitals, laboratory and radiological parameters were recorded. The primary outcome was mortality and secondary outcomes were duration of stay in hospital and complications, if any, developed during hospital stay.Results: Eighty-four cases were enrolled, with male to female ratio of 1:1. Mean age was46.40 19.59 years. The significant variables were: serum lactate (p